1989
DOI: 10.1002/ijc.2910440423
|View full text |Cite
|
Sign up to set email alerts
|

A short sequence, within the amino acid tandem repeat of a cancer‐associated mucin, contains immunodominant epitopes

Abstract: The polymorphic epithelial mucin (PEM) appears to be the target molecule for many monoclonal antibodies (MAbs) which react with tumour-associated and epithelium-specific antigens. PEM contains a large domain made up of 20 amino-acid tandem repeats which are highly immunodominant as many of the antibodies reactive with this molecule recognize epitopes within this area. Using overlapping peptide octamers, we have precisely mapped the epitopes of 4 MAbs reactive with the tandem repeats including one, SM-3, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
113
0
9

Year Published

1991
1991
2003
2003

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 226 publications
(128 citation statements)
references
References 16 publications
6
113
0
9
Order By: Relevance
“…MAb SM3 binds the pentapeptide PDTRP and the glycopen- tapeptide PDT( O -alpha-d-GalNAc)RP; these epitopes are recognized when the mucin is under-glycosylated (Burchell et al 1989;Möller et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…MAb SM3 binds the pentapeptide PDTRP and the glycopen- tapeptide PDT( O -alpha-d-GalNAc)RP; these epitopes are recognized when the mucin is under-glycosylated (Burchell et al 1989;Möller et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of the SM3 binding to MUC1 is apparently due to the core 2 branch masking the polypeptide PDTRP motif recognized by SM3 (10). This steric hindrance by the core 2 branch of access to the VNTR region of the MUC1 polypeptide could also explain the approximate 2-fold reduction in actual number of O-glycans attached to MUC1 in normal cells compared with T47D cells (6).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the cancer-associated glycoprotein is antigenically distinct from the normally processed mucins (7). This difference in antigenic profile is detected by the antibody SM3 (8,9), which recognizes a core protein epitope selectively exposed in the tandem repeat of the cancer-associated MUC1 mucin (10).…”
mentioning
confidence: 99%
“…26 Most react with a dominant epitope within the variable number of tandem repeats of the protein core; namely, the hydrophilic sequence of PDTRPAP. [26][27][28] The specificity of antibody binding to the protein core depends largely on the extent of MUC1 glycosylation; during the ISOBM TD-4 workshop, clusters of monoclonal antibodies were identified that distinguish between the various glycoforms of MUC1. 29 30 Although MUC1 is defined as an epithelial antigen, in 1984 Delsol et al reported that lymphoid cells and malignancies express EMA.…”
mentioning
confidence: 99%